Factors associated with high-risk pregnancy: role of environmental contaminants, Brazil. (30th September 2020) - Martins, L; Fernandes, J; Pamplona, Y; Barbieri, C; Vaz, J; Braga, A; Pereira, L
Abstract: Introduction: The Região Metropolitana da Baixada Santista (RMBS) is considered as a region with the worst maternal and child mortality rates in the state of São Paulo, Brazil. Besides this, RMBS has the worst rates of environmental contamination. High-Risk Pregnancy is one of the factors that lead to a higher chance of morbidity and mortality of the mother and fetus binomial. Objective: Evaluate the relationship between exposure to environmental contaminants and high-risk pregnancy. Methodology: Case-control study, using a probabilistic sample composed of 402 pregnant women divided into with and without high-risk pregnancy. The instrument used was a self-administered questionnaire and secondary data on contaminated areas obtained from the Environmental Company of the State of São Paulo. Descriptive analysis, Chi-square test, univariate and multiple logistic regression analysis were performed. The participants were also georeferenced by place of residence. Results: It was observed an association, by chi-square test between high-risk pregnancy and age over 35 years (p < 0.05), use of insecticide (p < 0.001), consumption of foods packed in plastics (p = 0.050) and manipulation with oil paint (p = 0.002). The final multiple logistic regression model demonstrated that those who live in contaminated areas are 2 times more likely to have a risk pregnancy (OR = 1.993; 95%CI: 1.02; 3.90), as well as identified as jointly important risk factors for pregnancy: working in health services (OR = 3.97 (95%CI: 1.00; 16.09)), use of insecticide (OR = 3.45 (95%CI: 1.66; 7.16)) and use of oil paint (OR = 6.96 (95%CI: 1.38; 35.09)). Conclusions: Environmental contaminants play an important role in pregnancy, and mitigating measures are needed to improve the environment and reduce high-risk pregnancy in RMBS. Key messages: Exposure to the environmental contaminants is an important rik factor in the pregnancy. The Região Metropolitana da Baixada Santista (RMBS) is considered as a region with the worst maternal and child mortality rates in the state of São Paulo, Brazil.